MINAT PENGGUNAAN ULANG LAYANAN DIGITAL BANKING DENGAN TECHNOLOGY ACCEPTANCE MODEL (TAM) - Indri Nurfitriani; Lilik Noor Yuliati; Megawati Simanjuntak (Jurnal Doktor Manajemen (JDM), 2023)
The rapid development of technology forces conventional banks or commercial banks to adopt digital technology in their business. Bank BTPN is one of the banks in Indonesia that has implemented digital technology in its services. Bank BTPN launched a digital banking product called Jenius. Jenius is a digital banking platform equipped with a VISA card that can help BTPN bank customers carry out financial activities via smartphones so that customers have control over their money and financial arrangements. This research was conducted to analyze behavioral intentions in using the Jenius digital banking platform services using the Technology Acceptance Model (TAM) method. The indicator variables used are perceived usefulness, perceived ease of use, brand image, co-creation, and attitude toward using. The results of this study are that brand image and attitude toward using have a significant direct effect on behavior intention to use, and attitude toward using are influenced by perceived usefulness, perceived ease of use, and co-creation.